Search for pair-produced leptoquarks in e e-interactions at GeV p. 281 - Lendermann, V; Schultz-Coulon, HC; Wegener, D; Asakawa, E; Hagiwara, K; Haug, E; Gonçalves, VP; Machado, MVT; Pietrycki, T; Szczurek, A; others (The European Physical Journal C-Particles and Fields, 2003)
n/a
n/a